2022
DOI: 10.54178/jsedmv4i1001
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Studies of Different Parameters as Markers for Nephropathy in Type 1 Diabetic Patients

Abstract: Albuminuria is the most characteristic marker of diabetic nephropathy (DN), which is a diabetic complication associated with DN progression. However, renal functions decreased by about one-third of diabetic patients before the occurrence of albuminuria. We study the role of telomere length (TL) of blood leukocytes, some inflammatory markers in the progression of DN in patients with type 1 diabetes (T1D). Volunteers were selected and distributed into four groups: group 1 included 20 healthy subjects as control,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…These processes may be associated with nephropathy. Moreover, these results are consistent with those of Gounden et al (2022) [39] and Soliman et al (2022) [40], who reported impaired renal function and nephrosis together with changes in these parameters in T1DM patients. Changes in lipid metabolism parameters in patients tended to increase atherogenic cholesterol fractions in both groups, which are negative factors for the course of DM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These processes may be associated with nephropathy. Moreover, these results are consistent with those of Gounden et al (2022) [39] and Soliman et al (2022) [40], who reported impaired renal function and nephrosis together with changes in these parameters in T1DM patients. Changes in lipid metabolism parameters in patients tended to increase atherogenic cholesterol fractions in both groups, which are negative factors for the course of DM.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are also consistent with Daehn (2018) [63] and Qi et al (2017) [25], who found increased oxidative damage in the glomerular endothelial cells (GECs) of DN patients, as urinary excretion of damaged oxidized DNA (8-OHdG) was significantly increased in patients with progressing DN. Soliman et al (2022) [40] showed increased values of this parameter in patients in the initial stages of DN, along with reduced values of telomere length. The results of studies in animals have shown that transforming growth factor-beta 1 levels, 8-hydroxy-2 -deoxyguanosine expression, and histopathological changes in renal tissue are increased in streptozotocin-induced diabetic rats [64].…”
Section: Discussionmentioning
confidence: 92%
“…Data on the correlation between 8-OHdG and leukocyte content in urine and the severity of DN development are of particular interest, which confirms the importance of using these markers for predicting DN development and progression in patients with DM [88]. Increased values of this parameter have been observed in patients in the initial stages of DN, along with reduced values of telomere length [89]. In patients with DM and DN, increased levels of AOPP, a marker of protein damage, have been found to be more significant than in patients with DM without DN [90].…”
Section: Dn and Os: Clinical Studiesmentioning
confidence: 70%